Employee Perceptions of Virtual Reality (VR) Training in the Metaverse: A Case Study in a Fintech Company - Kurniawan, Agung Widhi (Malaqbi Publisher, 2025)
This study examines employee perceptions of Virtual Reality (VR) training within a Jakarta-based fintech company, focusing on its effectiveness, challenges, and implications for equitable learning. Employing a qualitative case study approach, data were collected through participatory observation and semi-structured interviews with 25 employees engaged in a 12-week VR training program. Findings reveal that while VR enhances engagement and practical skill acquisition through immersive simulations, technical barriers, such as hardware discomfort, connectivity issues, and cognitive fatigue, pose significant challenges. Additionally, disparities in technological literacy and resource access underscored equity concerns, particularly among junior and non-technical staff. Despite these hurdles, collaborative VR modules fostered peer learning and motivation, though participants emphasized the irreplaceable value of human interaction in training. The study advocates for human-centered design principles, urging organizations to adopt participatory approaches and hybrid models that integrate VR with traditional mentoring. By addressing infrastructural and inclusivity gaps, fintech companies can harness VR’s potential to create adaptive, equitable training ecosystems in the metaverse era.